Rapid Decolorization of Cobalamin - Falah H. Hussein; Ahmed F. Halbus (International Journal of Photoenergy)
The photocatalytic decolorization of cobalamin was carried out in aqueous solution of different types of catalysts including ZnO, TiO2 (Degussa P25), TiO2 (Hombikat UV100), TiO2 (Millennium PC105), and TiO2 (Koronose 2073) by using UVA source of irradiation. The effect of various parameters such as photocatalyst amount, cobalamin concentration, type of catalyst, pH of aqueous solution, light intensity, addition of H2O2, flow rate of O2, type of current gas, and temperature on photocatalytic oxidation was investigated. The results indicated that the photocatalytic decolorization of cobalamin was well described by pseudo-first-order kinetics according to the Langmuir-Hinshelwood model. The effect of temperature on the efficiency of photodecolorization of cobalamin was also studied in the range 278–298 K. The activation energy was calculated according to Arrhenius plot and was found equal to  kJ·mol−1 for ZnO and  kJ·mol−1 for TiO2 (Degussa P25). The results of the total organic carbon (TOC) analysis indicate that the rate of decolorization of dye was faster than the total mineralization. Decolorization and mineralization of cobalamin in the absence of light and/or catalyst were performed to demonstrate that the presence of light and catalyst is essential for the decolorization of this cobalamin. The results show that the activity of different types of catalysts used in this study was of the sequence: ZnO > TiO2 (Degussa P25) > TiO2 (Hombikat UV100) > TiO2 (Millennium PC105) > TiO2 (Koronose 2073).